Succession, regression and loss: does evidence of saltwater exposure explain recent changes in the tree communities of North Carolina's Coastal Plain?. (6th April 2019) - Ury, Emily A; Anderson, Steven M; Peet, Robert K; Bernhardt, Emily S; Wright, Justin P
Abstract: Background and Aims: Coastal plant communities globally are highly vulnerable to future sea-level rise and storm damage, but the extent to which these habitats are affected by the various environmental perturbations associated with chronic salinization remains unclear. In this study, we examine the relationship between North Carolina wetland tree community composition and basal area change and indicators of salinization such as soil salt ion content and elevation. Methods: We surveyed 34 forest plots in forested, freshwater wetlands across the Albemarle–Pamlico Peninsula. A subset of our study sites had been sampled during the previous decade as part of the Carolina Vegetation Survey, enabling us to investigate the environmental effects on current community structure, and community change over time. Key Results: Multi-variate (ordination) analysis and linear regression models of tree community composition revealed that elevation and soil salt content were correlated with changes in total site tree basal area. Shifts in tree community composition were, however, only weakly correlated with indicators of salinization, specifically elevation, soil sulphate and sodium, but not chloride. While the majority of plots experienced gains in basal area over the past decade, consistent with secondary succession, sites with high soil salt content or low elevation experienced basal area (biomass) loss during the same period. Conclusions: The key factors associated with chronic saltwater intrusion (soil ion content) likely explain recent changes in tree biomass, and potential shifts in community composition in low-elevation sites along the North Carolina coast. Not only is it probable that other coastal forest ecosystems worldwide will experience similar stressors and shifts in community biomass and structure as sea levels rise, but the ability of these habitats to deliver key ecosystem services like carbon sequestration and flood defence will be compromised as a result.